GOOD CORPORATE GOVERNANCE DAN RASIO HUTANG PERUSAHAAN - Novi Runiati; Tina Sulistiyani (Universitas Ahmad Dahlan, 2014)
The aim of this research is to investigate the influence of corporate governance, and firm size to leverage. Good corporate governance that used in this research is Corporate Governance Perception Index (CGPI). The independent variable that use in this research is leverage such as Debt to Total Aktiva and Debt to Total Shareholder Equity. The sample in this research are companies which were listed in Corporate Governance Perception Indeks in the year of 2010-2013 in SWA Magazine of publication. Total sample in this research are 11 companies that selected with purposive sampling method. This research uses multiple regression analysis method to investigate the influence of corporate governance and firm size to leverage. The results of this research indicate that good corporate governance had negative significant influence to debt to total aktiva and total shareholder equity. The firm size had no significant influence to debt to total aktiva and total shareholder equity.